Laparoscopic repair of traumatic intraperitoneal bladder rupture: a rare case report - Udit Jain; Kumar, Dinesh; Sreedhar; Qazi, Ifrah Ahmad; Rasool, Mustaq (International Journal of Research in Medical Sciences, 2023)
Laparoscopic repair of traumatic intraperitoneal bladder rupture is safe and effective technique. We here report case of 49 year male with traumatic intraperitoneal bladder rupture proven by CT urogram after sustaining blunt trauma abdomen injury, repaired by laparoscopy technique. Patient recovered without any complications and was discharged on postoperative day 6 under stable condition. we here by conclude that if bladder injury identified early and conditions if feasible, laparoscopic repair is one of the good options for further management without involving open laparotomy.